SURVIVAL ANALYSIS OF PEDIATRIC RENAL TUMORS: THE ROLE OF TUMOR BIOLOGY AND SURGICAL INTERVENTION (Herald of the National Children's Medical Center, 2025)
This study aimed to identify prognostic factors influencing survival outcomes in pediatric oncology patients treated at a tertiary-level hospital in Tashkent, Uzbekistan. A retrospective cohort of 108 children diagnosed with kidney tumors was analyzed using Cox proportional hazards regression. Eight cases (7.4%) were excluded due to missing data, leaving 100 patients for analysis. The cohort included 49 males (45%) and 59 females (55%), with a median age of 2.07 years (IQR: 0.95–4.01).Tumor characteristics were predominantly primary tumors in 88 patients (88%), while progressive tumors were observed in 10 patients (10%) and non-primary tumors in 4 patients (4%). Local growth into neighboring organs was detected in 40 cases (40%), and metastasis to distant organs was observed in 28 cases (28%). Histological analysis revealed nephroblastoma (Wilms tumor) as the most common diagnosis, accounting for 95 cases (95%), followed by mesoblastic nephroma in 3 cases (3%) and adenocarcinoma in 1 case (%). Data on histology were unavailable for 1 case (1%).
Keywords: pediatric oncology; kidney tumors; survival analysis; Wilms tumor; nephroblastoma; prognostic factors